2012
DOI: 10.1111/j.1477-2574.2012.00439.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of one- vs. two-stage laparoscopic/endoscopic management of common bile duct stones

Abstract: Outcomes after one-stage laparoscopic/endoscopic management of bile duct stones are no different to the outcomes after two-stage management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(52 citation statements)
references
References 24 publications
1
50
0
1
Order By: Relevance
“…This was in agreement with several studies that reported a morbidity rate of 8-19% and a mortality rate of around 0-1% [15]. This was in contrast to the study carried out by Shojaiefard et al, who reported 5.55% morbidity but 0% mortality [20].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This was in agreement with several studies that reported a morbidity rate of 8-19% and a mortality rate of around 0-1% [15]. This was in contrast to the study carried out by Shojaiefard et al, who reported 5.55% morbidity but 0% mortality [20].…”
Section: Discussionsupporting
confidence: 92%
“…A similar study carried out by Alexakis and Connor denoted a success rate of 80-91% [15]. In another study by Lu et al, success rates of 89-95% were reported [9].…”
Section: Discussionmentioning
confidence: 61%
“…An analysis comparing two-stage treatment by laparoscopic cholecystectomy followed by endoscopic stone removal with one-stage laparoscopic treatment also found no differences other than length of hospital stay [160]. A metaanalysis of nine RCTs including 933 patients comparing one-stage and two-stage treatment for endoscopic stone removal found no differences in stone removal rate, complication rate, mortality, or other parameters [126]. The analysis concluded that the costs of the procedures could not be compared because different methods were used to calculate the costs in different countries and regions.…”
Section: Commentarymentioning
confidence: 99%
“…The surgical procedures in this meta-analysis included open (seven trials) and laparoscopic (five trials) procedures, and the subanalysis also did not reveal any differences. When cholecystectomy was performed at the same time as the treatment for choledocholithiasis, the hospital stay was reduced compared with two-stage treatment despite there being no difference in the stone removal rate [126,127]. However, a prospective national survey conducted by the Japan Biliary Association Scientific Committee [128] (literature published outside the search period) reported that only 3 of 77 cases of choledocholithiasis were treated surgically (3.9%), one with laparoscopic surgery and two with open choledochotomy.…”
Section: Commentarymentioning
confidence: 99%
“…Another meta-analysis [83] included RVT in the so-called one-stage procedure, merging studies regarding LCBDE and comparing this group to the two-stage procedures (LC preceded or followed by ERCP). Again, no statistically detectable differences in patients' outcomes were recorded between the two strategies.…”
Section: Concomitant Laparoscopic Cholecystectomy and Common Bile Ducmentioning
confidence: 99%